2007
DOI: 10.1021/cr050946x
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalysis in Ionic Liquids

Abstract: Fred van Rantwijk (1943) studied organic chemistry at the Delft University of Technology, where he remained as a staff member. He received his Ph.D. in 1980, for work under the guidance of Professor H. van Bekkum. Since the late 1980s he has been working on the application of enzymes in organic synthesis. His particular research interests are the use of enzymes in nonnatural reactions and nonnatural media, enzyme immobilization, and transformations using multi-enzyme systems.Roger Sheldon (1942) received a Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
865
0
21

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,485 publications
(896 citation statements)
references
References 219 publications
10
865
0
21
Order By: Relevance
“…Many literature surveys are available to different audiences spanning disciplines from asymmetric catalysis, homogeneous catalysis, organic synthesis, green chemistry, biotransformations, analytical chemistry, industrial applications, enzymatic reactions and others. [3][4][5][6][7][8][9][10][11][12] Despite all advances on the basic properties, comprehension and use of ILs, there are still many things left to be achieved. And, somewhat surprising, their physical and chemical properties still have many issues under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Many literature surveys are available to different audiences spanning disciplines from asymmetric catalysis, homogeneous catalysis, organic synthesis, green chemistry, biotransformations, analytical chemistry, industrial applications, enzymatic reactions and others. [3][4][5][6][7][8][9][10][11][12] Despite all advances on the basic properties, comprehension and use of ILs, there are still many things left to be achieved. And, somewhat surprising, their physical and chemical properties still have many issues under debate.…”
Section: Introductionmentioning
confidence: 99%
“…The initial interest on ILs as alternative extractive fluids results from their physical and chemical advantages, namely negligible flammability and vapour pressure, high solvation ability, high chemical stability, high selectivity, and easiness in recovering and recycling them [25][26][27][28][29]. Moreover, it was already shown that adequate ILs do not significantly inactivate enzymes ensuring thus their structural integrity and enzymatic activity [5,27].…”
Section: Introductionmentioning
confidence: 99%
“…31,33,34 While the hydrophobic effect that increases protein stabilization is absent in organic ionic liquids, one advantage to biocatalysis in ILs as opposed to aqueous buffers is the longer activity of enzymes in ILs, which is thought to arise from the slow breaking and remaking of hydrogen bonds in the nonaqueous medium. 35 Studies of cellulase-induced catalysis in ionic liquids are, however, still limited. 5,[36][37][38][39] The physical and chemical properties of ionic liquids vary considerably depending on their cation-anion pair.…”
Section: Introductionmentioning
confidence: 99%